KONFLIK SEPARATISME PAPUA DAN IMPLIKASINYA TERHADAP HUBUNGAN DIPLOMASI INDONESIA-AUSTRALIA - Sinaga, Marta Ulina; Saeri, M. (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
This paper will explain the conflict of separatism and its implications for the diplomatic relations between Indonesia and Australia. Papua's growing separatism conflict abroad led to the emergence of the internationalization of separatism issues in Papua. The increase in Indonesian diplomacy is expected to be Indonesia's way of maintaining the sovereignty of countries including Papua.This study uses the perspective of constructivism and the theory of constructivism. The theory used in this study is qualitative research method using descriptive analysis. While data collection is launched with library research techniques consisting of books, news, journals and trusted websites. This research proves that Indonesia is making efforts to improve diplomatic relations to Australia to suppress intervention in the Papua case by cooperating in several areas such as economy, health and education. Keywords: Papua, Conflict, Separatism, Diplomacy